Politeness in Language of Riau Malay Students: A Linguistic Phenomenon (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to gain an in-depth understanding of the phenomenon of politeness in the language of Riau Malay students. This study was qualitative with a phenomenological method. The data were obtained through recordings of student speech acts and semi-structured interviews with 48 students. Data analysis phenomenological data analysis was carried out in several stages, namely (a) Initial stage: fully describing the phenomena experienced by the research subject. All recorded speech act data and in-depth interviews with research subjects were transcribed into written language. (b) In this study, the reduction stage was carried out in two ways: eudetic reduction and phenomenological reduction. Eudetic reduction is made by reducing the recorded speech act data that has been transcribed from spoken language to written language. In eudetic reduction, values, ideologies, norms, or meanings will be found from the students' recorded speech acts. Meanwhile, the phenomenological reduction carried out on interviews with students related to politeness in speech acts. The results showed that the politeness phenomenon that occurs in student speech is motivated by several factors. First, different views from students about politeness are motivated by culture and the environment in which they live. Second, the habit of speaking in the way they speak. Third, their understanding of the narrative context.